Analysis and Design of Queues Using Multi Phase Methods to Optimize Motor Vehicle Tax Services (Case Study of Samsat UPT BAPENDASU) - Firmansyah, Denny; Sary, Yoshida (Bahasa Indonesia, 2024)
The research aims to (1) characterize the queuing system which will be built using the multi-phase method, (2) improve the information and communication system and provide up to date information and help in increasing the efficiency and effectiveness of services in the queuing process at the UPT BAPENDASU Samsat. The research method uses quantitative research. The data analysis technique uses Kolmogorov-Smirnov to check that the data is Poisson distributed. Data collection was carried out using literature studies and field studies, namely (observation, interviews and document study). The researchers obtained the results that (1) The implementation of the multi-phase method had a significant positive impact, to achieve less than 10 minutes, the value of the service rate for each phase was not much different (2) In order to increase the efficiency and quality of service at the BAPENDASU UPT Samsat, the research This research has investigated and implemented a multi-phase method to optimize the queuing process in motor vehicle tax services.